Cognitive Task Performance During Titration Predicts Deep Brain Stimulation Treatment Efficacy: Evidence From a Case Study - Weichart, Emily R.; Sederberg, Per B.; Sammartino, Francesco; Krishna, Vibhor; Corrigan, John D.; Rezai, Ali R. (Frontiers in Psychiatry, 2020)
Device titration is a major challenge when using deep brain stimulation (DBS) for behavioral disorders. Unlike in movement disorders, there is no reliable real-time clinical feedback for changes in complex behaviors resulting from DBS of the nucleus accumbens. Here, a female patient receiving DBS of the nucleus accumbens for the treatment of morbid obesity underwent cognitive testing via the flanker task alongside traditional methods of device titration. One set of stimulation parameters administered during titration resulted in acute cognitive improvement (p=0.033) and increased frontal engagement as measured by electroencephalography (left anterior: p=0.007, right anterior: p=0.005) relative to DBS-OFF. The same parameters resulted in the most weight-loss during long-term continuous stimulation (47.8lbs lost in 129 days) compared to the results of other stimulation settings. Diffusion tensor imaging analyses showed increased connectivity to dorsal attention networks and decreased connectivity to the default mode network for optimal parameters (p<0.01). Our results provide evidence that targeted cognitive testing is a potentially useful tool for capturing acute effects of DBS stimulation during titration and predicting long-term treatment outcomes. ClinicalTrials.gov Identifier: NCT01512134, https://clinicaltrials.gov/ct2/show/NCT01512134